PRIMARY TREATMENT STOCHASTIC VIMIRUVALLY INFORMATION BY MATLAB - Burichenko, M. Yu.; Sushenko, O. A (Problems of Informatization and Management, 2021)
The content of the stages of primary processing of stochastic measuring information is described, the program interface is described and fragments of program texts are given. A method for determining interactive expressions of fractional-rational functions that approximate the spectral densities of stochastic signals in the interactive mode is described.